Effects of acupressure therapy period towards blood sugar level in type 2 diabetes mellitus patients at Lumajang acupressure clinic - Anung Putri Illahika; Hean Safira (Qanun Medika - Jurnal Kedokteran FK UMSurabaya, 2021)
Abstract  Diabetes Mellitus is a worldwide metabolic disease and becomes a challenge for the health practitioner. Unfortunately, less than half of these diabetic individuals are aware of their conditions, and less than 1% of those receiving medical treatment achieve their therapeutic targets. Acupressure is an alternative method that is believed to be an effective way of treating diabetic patients with reducing symptoms and complications. This research aims to discover the effect of period acupressure therapy on blood sugar levels in type two diabetes mellitus patients in Lumajang Acupressure Clinic. It uses an observational analytic design with pre-test and post-test approach. It involved 36 participants who were split into two groups and contained 18 participants for each group. The first group received acupressure therapy for three weeks, while the second group received eight weeks. Both groups underwent acupressure at the San Yin Jiao (SP-6) acupoint for 20 minutes three times a week. All participants in both groups had their blood glucose checked before and after acupressure therapy. The results showed that the two groups were significantly different for the paired t-test and the independent t-test. The acupressure therapy period has an effect on decreasing blood sugar levels in type two diabetes mellitus patients at Lumajang acupressure clinic. Keywords             : Acupressure, the period of therapy, blood glucose level, type two diabetes mellitusCorrespondence   : Anungputri113@gmail.com